Outcomes and phenotypic expression of rare variants in hypertrophic cardiomyopathy genes in over 200, 000 adults. (14th October 2021) - De Marvao, A; McGurk, K; Zheng, S; Thanaj, M; Bai, W; Duan, J; Halliday, B; Pantazis, A; Prasad, S; Rueckert, D; Walsh, R; Ho, C; et al.
Abstract: Background: Hypertrophic cardiomyopathy (HCM) is caused by rare variants in sarcomere-encoding genes, but little is known about the clinical significance of these variants in the general population. Purpose: To determine the population prevalence of HCM-associated sarcomeric variants, characterise their phenotypic manifestations, estimate penetrance, and identify associations between sarcomeric variants and clinical outcomes, we performed an observational study of 218, 813 adults in the UK Biobank (UKBB), of whom 200, 584 have whole exome sequencing (WES). Methods: We carried out an integrated analysis of WES and cardiac magnetic resonance (CMR) imaging in UK Biobank participants stratified by sarcomere-encoding variant status. Computer vision techniques were used to automatically segment the four chambers of the heart (Figure 1). Cardiac motion analysis was used to derive strain and strain rates. Regional analysis of left ventricular wall thickness was performed using three-dimensional modelling of these segmentations. Results: Median age at recruitment was 58 (IQR 50–63 years), and participants were followed up for a median of 10.8 years (IQR 9.9–11.6 years) with a total of 19, 507 primary clinical events reported. The prevalence of rare variants (allele frequency <0.ehab724.17314) in HCM-associated sarcomere-encoding genes in 200, 584 participants was 2.9% (n=5, 727; 1 in 35), and the prevalence of pathogenic or likely pathogenic variants (SARC-P/LP) was 0.24% (n=474, 1 in 423). SARC-P/LP variants were associated with increased risk of death or major adverse cardiac events (MACE) compared to controls (HR 1.68, 95% CI 1.37–2.06, p<0.001), mainly due to heart failure endpoints (Figure 2: cumulative hazard curves with zoomed plots for lifetime risk of A) death and MACE or B) heart failure, stratified by genotype; genotype negative (SARC-NEG), carriers of indeterminate sarcomeric variants (SARC-IND) or SARC-P/LP; C) Forest plot of comparative lifetime risk of clinical endpoints by genotype). While males had a higher overall risk of adverse outcomes, the incremental genetic risk from SARC-P/LP mutations was greater in females (HR for females: 2.18 CI 1.65–2.89, p<0.001; HR for males: 1.42 CI 1.05–1.9, p=0.02). In 21, 322 participants with CMR, SARC-P/LP were associated with asymmetric increase in left ventricular maximum wall thickness (10.9±2.7 vs 9.4±1.6 mm, p<0.001) but hypertrophy (≥13mm) was only present in 16% (n=7/43, 95% CI 7–31%). Other rare sarcomere-encoding variants had a weak effect on wall thickness (9.5±1.7 vs 9.4±1.6 mm, p=0.002) with no combined excess cardiovascular risk. Conclusions: In the general population, SARC-P/LP variants have low aggregate penetrance for overt HCM but are associated with increased risk of adverse cardiovascular outcomes and a sub-clinical cardiomyopathic phenotype. Although absolute event rates are low, identification of these variants may enhance risk stratification beyond familial disease. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): The study was supported by the Medical Research Council, UK (MC-A651-53301); National Institute for Health Research (NIHR) Imperial College Biomedical Research Centre; NIHR Royal Brompton Cardiovascular Biomedical Research Unit; British Heart Foundation (NH/17/1/32725, RG/19/6/34387, RE/18/4/34215).